PROBLEMS IN TRANSLATION (Academia Science Repository, 2023)
Today's in the day globalization and cross-cultural of communications fast development, international connections expanded to go own from himself of translation studies present period demand and his in society take your place grow up to go means. Of course, any process owns in turn known to problems face will come This in the article in translation studies meeting standing problems illuminated.